Echocardiographic Evaluation of Hemodynamics in Neonates and Children - Singh, Yogen (Frontiers in Pediatrics, 2017)
Hemodynamic instability and inadequate cardiac performance are common in critically ill children. The clinical assessment of hemodynamic status is reliant upon physical examination supported by the clinical signs such as heart rate, blood pressure, capillary refill time, and measurement of the urine output and serum lactate. Unfortunately, all of these parameters are surrogate markers of cardiovascular well-being and they provide limited direct information regarding the adequacy of blood flow and tissue perfusion. A bedside point-of-care echocardiography can provide real-time hemodynamic information by assessing cardiac function, loading conditions (preload and afterload) and cardiac output. The echocardiography has the ability to provide longitudinal functional assessment in real-time, which makes it an ideal tool for monitoring hemodynamic assessment in neonates and children. It is indispensable in the management of patients with shock, pulmonary hypertension and patent ductus arteriosus. The echocardiography is the gold standard diagnostic tool to assess hemodynamic stability in patients with pericardial effusion, cardiac tamponade and cardiac abnormalities such as congenital heart defects or valvar disorders. The information from echocardiography can be used to provide targeted treatment in intensive care settings such as need of fluid resuscitation versus inotropic support, choosing appropriate inotrope or vasopressor, and in providing specific interventions such as selective pulmonary vasodilators in pulmonary hypertension. The physiological information gathered from echocardiography may help in making timely, accurate and appropriate diagnosis, and providing specific treatment in sick patients. There is no surprise that use of bedside point-of-care echocardiography is rapidly gaining interest among neonatologists and intensivists, and it is now being used in clinical decision making for patients with hemodynamic instability. Like any other investigation, it has certain limitations and the most important limitation is its intermittent nature. Sometimes acquiring high quality images for precise functional assessment in a ventilated child can be challenging. Therefore, it should be used in conjunction with the existing tools (physical examination and clinical parameters) for hemodynamic assessment whilst making clinical decisions.